2018
DOI: 10.1021/acsomega.7b01973
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Biocatalysis by High-Throughput Protein Engineering Using Droplet Microfluidics Coupled to Mass Spectrometry

Abstract: Directed Evolution is a key technology driving the utility of biocatalysis in pharmaceutical synthesis. Conventional approaches to Directed Evolution are conducted using bacterial cells expressing enzymes in microplates, with catalyzed reactions measured by HPLC, high-performance liquid chromatography-mass spectrometry (HPLC-MS), or optical detectors, which require either long cycle times or tailor-made substrates. To better fit modern, fast-paced process chemistry development where solutions are rapidly neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 34 publications
(71 reference statements)
0
93
0
2
Order By: Relevance
“…Droplet microfluidics enables experiments to be performed at nanoliter to femtoliter scale, increasing throughput and decreasing unit costs of chemical and biological experimentation . A decade of research in the field has demonstrated the utility of droplet systems for a range of applications, including single cell gene expression profiling, small molecule screening, and diagnostics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Droplet microfluidics enables experiments to be performed at nanoliter to femtoliter scale, increasing throughput and decreasing unit costs of chemical and biological experimentation . A decade of research in the field has demonstrated the utility of droplet systems for a range of applications, including single cell gene expression profiling, small molecule screening, and diagnostics .…”
Section: Introductionmentioning
confidence: 99%
“…FADS has found use in ultrahigh throughput screening for directed evolution . Screening large libraries is often the rate‐limiting step in biocatalyst development, where thousands of enzyme variants must be tested for catalytic activity, and plate based screens are time and resource intensive. FADS has enabled screening of libraries containing millions of variants in a few hours.…”
Section: Introductionmentioning
confidence: 99%
“…These droplets can be directly interfaced to an ESI source for MS-based screening at a rate of < 1 s ( Fig. 1b) [24,29]. To achieve robust screening, it is necessary to perform systematic optimization of many parameters including flow rate, emitter configuration, and droplet-stabilizing surfactants [29].…”
Section: Basic Concepts In Ms and High-throughput Ms Approachesmentioning
confidence: 99%
“…Droplet microfluidics enables experiments to be performed at nanoliter to femtoliter scale, increasing throughput and decreasing unit costs of chemical and biological experimentation . A decade of research in the field has demonstrated the utility of droplet systems for a range of applications, including single cell gene expression profiling, small molecule screening, and diagnostics .…”
Section: Introductionmentioning
confidence: 99%
“…MS offers nearly universal label‐free detection with high sensitivity and selectivity, as well as the flexibility for multiplexing. Recent work with ESI and matrix‐assisted laser desorption/ionization (MALDI) MS has shown that MS can be used for droplet analysis; however, sample destruction by ESI has been an obstacle to coupling it to microfluidic droplet sorting.…”
Section: Introductionmentioning
confidence: 99%